Design e gênero: diretrizes metodológicas para validação do uso da linguagem visual na roupa infantil - Bezerra, Marcela Fernanda de Carvalho Galvao Figueiredo [UNESP] (2014)
In this research proposal, the presence of visual language as applied to children's clothing transmitting element of information about gender was observed for this audience. The research sought to make a reading of the children's visual elements inserted shirts, in order to understand gender relations applied to them and how they are understood by children, whether girls or boys. The study observed 88 children from two local nurseries in Caruaru - Pernambuco and, through an innovative methodological approach aimed at children, purpose foster the development of products manufactured in Polo Clothing Wasteland to consider the needs and understandings of children during a stage of its development. The investigation was conducted by considering three points in particular: i) a comprehensive and interdisciplinary theoretical foundation - that tangenciou various thematic areas; ii) the methodology adapted to the target audience of children's early childhood - by respecting their preference and constraints over the data collection; and, iii) construction based on the qualitative and quantitative and qualitative observations of research data readings. At the end, the approach provides results in two ways: 1) by suggesting preferences in terms of age approached - three, four or five years - and 2) to observe the choice related to the child's gender. As the outcome of the investigation, were proposed guidelines that suggest ways of approaches and elements related to the use of colors, shapes and textures in children's apparel. The study aims to stimulate the application of design tools in the production or the Polo Clothing Wasteland and appears as a first step towards the emergence of new possibilities for research that addresses gender issues embedded in clothing or products for children